The integral role of the clinical pharmacist in drug-assisted intubation at a newly established children’s major trauma center - Kevin Enright (9584809) (2022)
This commentary outlines how the clinical pharmacist can support the safe administration of emergency medications in trauma anesthesia for seriously injured children. Promoting the professional development of the clinical pharmacist provided an opportunity to strengthen a key step in our trauma care pathway. We describe the implementation of this process in a new hospital, which was to become the designated children’s trauma center for an entire country. Although the literature documents the use of pharmacists in emergency intubation, ours was a unique set of circumstances, where empowering the pharmacist in frontline clinical care provided additional quality assurance for rapid sequence induction and intubation in trauma. Medical simulation was a core part of socializing the advanced clinical practice role of pharmacy within the trauma team. It was our experience that the pharmacist helps to promote confidence and decision making among other members of the trauma team. Other Information Published in: International Journal of Clinical Pharmacy License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s11096-021-01262-x